PENGARUH pH LENDIR MUKOSA VAGINA SAAT BIRAHI TERHADAP PERSENTASE KEBUNTINGAN (Conception Rate) PADA SAPI PERAH DI KUD TANI WILIS KABUPATEN TULUNGAGUNG DAN KSU TUNAS SETIA BARU KABUPATEN PASURUAN - Rizki, Andaru; Srianto, Pudji; Suprihati, Endang; Sardjito, Trilas; Ismudiono, Ismudiono; Al Arif, Mohammad Anam (Universitas Airlangga, 2019)
The purpose of this research is to determine the effect of mucos acidity of vaginal mucous when estrus towards conception rate at KUD Tani Wilis Tulungagung District and KSU Tunas Setia Baru Pasuruan District. Measured samples were taken from 30 dairy cattles in each KUD. Mucos acidity of vaginal mucous were obtained by using a digital acidity meter before insemination was done on dairy cattle. After measuring the acidity from mucosal vagina mucous, artificial insemination has done on estrus dairy cattle. On the 60th day after insemination, rectal palpation was done to check the conception rate. Research result from 30 dairy cattle on each KUD showed that mucos acidity of vaginal mucous has signifficant effect towards conception rate. Mucos acidity of vaginal mucous range 6.5-8.5 with the highest range of conception rate in KSU Tunas Setia Baru Pasuruan District 7.5-7.7 and in KUD Tani Wilis Tulungagung District with the highest range of conception range 7.2-7.4 and 7.5-7.7.